O Acordo de leniência como mecanismo legal para o desenvolvimento: estratégia de efetivação para recuperação de ativos desviados pela corrupção - Guedes Neto, Luiz do Nascimento (2019)
The following paper aim on the analysis of the Business Anti-corruption Law n° 12.846/2013, to understand how, through the Leniency Agreement, devious resources from corruption are redeemed, and in what way they support the social development, whereas development not the economical growth, but the expansion of the individual liberties from the assurance of the fundamental rights for the society. From this premise, is intended to discuss about the modern conceptions of development, noticing it as means and ends of distincts liberties, according to the concepcion of Amartya Sen (2010). Furthermore, the analysis of corporative system corruption, as it acts like a barrier to the economical development, from the capital diversion that could be used for this purpose, but ends up being utilized for third-party enrichment. This corrupt system is an invisible type of violence, that feeds itself from the nonstop connection between corrupted individuals by the capital in business relationships that seeks mutual benefits, not only financial, but contracts, favors and power. The Business Anti-corruption Law comes up in this scenario intending to interrupt this vicious cycle not only with punishments for corrupt activities, but also with the creation of strategies that aim the recover of resources deviated, from the Leniency Agreement and adoption of Compliance of the companies. This dissertation discourse about the effectiveness of retrieval of this amounts from that agreement, seeking make explicit the paths covered through the rescued resources, as elaborating strategies of reuptake effectiveness to sustainable development, through means that result in liberties expansion.